2017
DOI: 10.1186/s13287-016-0464-3
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin attenuates total body irradiation-induced hematopoietic system injury in mice via inhibition of oxidative stress and apoptosis

Abstract: BackgroundThe hematopoietic system is especially sensitive to total body irradiation (TBI), and myelosuppression is one of the major effects of TBI. Astaxanthin (ATX) is a powerful natural anti-oxidant with low toxicity. In this study, the effect of ATX on hematopoietic system injury after TBI was investigated.MethodsFlow cytometry was used to detect the proportion of hematopoietic progenitor cells (HPCs) and hematopoietic stem cells (HSCs), the level of intracellular reactive oxygen species (ROS), expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 39 publications
3
65
0
Order By: Relevance
“…Moreover, we previously showed the CAA protective capacity exerted by algae natural astaxanthin in human endothelial cells subjected to oxidative stress in vitro [ 51 ]. Recently, Xue et al [ 70 ] demonstrated that astaxanthin treatment markedly attenuated mitochondrial ROS produced after total body irradiation. Moreover, a potent mitochondrial ROS reduction had been noticed when using targeted than nontargeted mitochondrial antioxidants in different in vitro and in vivo models [ 64 , 70 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we previously showed the CAA protective capacity exerted by algae natural astaxanthin in human endothelial cells subjected to oxidative stress in vitro [ 51 ]. Recently, Xue et al [ 70 ] demonstrated that astaxanthin treatment markedly attenuated mitochondrial ROS produced after total body irradiation. Moreover, a potent mitochondrial ROS reduction had been noticed when using targeted than nontargeted mitochondrial antioxidants in different in vitro and in vivo models [ 64 , 70 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Xue et al [ 70 ] demonstrated that astaxanthin treatment markedly attenuated mitochondrial ROS produced after total body irradiation. Moreover, a potent mitochondrial ROS reduction had been noticed when using targeted than nontargeted mitochondrial antioxidants in different in vitro and in vivo models [ 64 , 70 74 ]. In contrast to synthetic astaxanthin, natural astaxanthin without purification also contains other carotenoids, and there is no much evidence confirming the fact that these carotenoids act in synergy, in an additive manner or possibly cancel each other [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…10 Furthermore, AST improves liver function 11 and destroys peroxide chain reactions to protect cells from oxidative damage. 12,13 AST also affects ultraviolet A (UVA) radiation as well as desquamation of the epidermis and the extracellular matrix of the dermis. 14 In addition, it improves heart function 15 by increasing the production of antibodies and T-cells, inflammation and age-related macular degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are very few agents that can effectively rescue HSCs from radiation injury when given after radiation exposure [ 10 ]. Antioxidant and HSC growth factors have limitations, and the major drawback of these agents is that they should be administrated before radiation or immediately after radiation [ 33 35 ]. There is an unmet medical need for identifying and developing effective agents that can be used to rescue lethal-dose radiation injury and enhance all-lineage hematopoietic cell recovery when given after irradiation.…”
Section: Discussionmentioning
confidence: 99%